2010
DOI: 10.1103/physreve.82.036118
|View full text |Cite
|
Sign up to set email alerts
|

Competitive market for multiple firms and economic crisis

Abstract: Abstract:The origin of economic crises is a key problem for economics. We present a model of long-run competitive markets to show that the multiplicity of behaviors in an economic system, over a long time scale, emerge as statistical regularities (perfectly competitive markets obey Bose-Einstein statistics and purely monopolistic-competitive markets obey Boltzmann statistics) and that how interaction among firms influences the evolutionary of competitive markets. It has been widely accepted that perfect compet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 24 publications
(9 reference statements)
1
51
0
2
Order By: Relevance
“…Because the firm consists of labor and capital, the Cobb-Douglas aggregate production function (or GDP) of neoclassical economics can be written in the form (Tao 2010(Tao , 2016):…”
Section: Technological Progress and Entropymentioning
confidence: 99%
“…Because the firm consists of labor and capital, the Cobb-Douglas aggregate production function (or GDP) of neoclassical economics can be written in the form (Tao 2010(Tao , 2016):…”
Section: Technological Progress and Entropymentioning
confidence: 99%
“…. ; n. Similar to statistical physics in which the internal energy UðN p ; SÞ can be written as a function of the number of particles, N p and the entropy S, Tao 10,17 suggested that the total revenue (or gross value of output) of N¯rms (or agents), Å, can be written as a function of N and the technological progress T ; that is,…”
Section: De¯nition 2 a Competitive Economy Is Called A Monopolistic mentioning
confidence: 99%
“…This means that the improvement of technological progress of a society is due to the degree of freedom that social members have experienced. 10,17 Equation (16) clearly predicts the revenue distribution among agents (or¯rms) in a competitive economy. Hence, we can compare it with the household income (like the revenue of self-employed¯rm) data.…”
Section: De¯nition 2 a Competitive Economy Is Called A Monopolistic mentioning
confidence: 99%
See 1 more Smart Citation
“…", about fairness and about opportunities, versus corruption and crony economics [1][2][3][4][5][6][7] (see footnote a). Clearly, there are other economical and sociological functions and indicators that are valuable in describing nations [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] and freedom 8 and democracy 6 are in°uencing lives much more. Yet, the income distribution, and the distributions derived from that, the \wealth distribution" and the \control on the°ow of wealth distribution", are clearly among the basic most in-°u ential quantities and should be researched on.…”
Section: Introductionmentioning
confidence: 99%